2009
DOI: 10.1093/cercor/bhp162
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Organization of Connections between the Temporal Cortex and Pulvinar Nucleus of the Tree Shrew

Abstract: We examined the synaptic organization of reciprocal connections between the temporal cortex and the dorsal (Pd) and central (Pc) subdivisions of the tree shrew pulvinar nucleus, regions innervated by the medial and lateral superior colliculus, respectively. Both Pd and Pc subdivisions project topographically to 2 separate regions of the temporal cortex; small injections of anterograde tracers placed in either Pd or Pc labeled 2 foci of terminals in the temporal cortex. Pulvinocortical pathways innervated layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 76 publications
4
62
0
Order By: Relevance
“…We compared the data collected in the present study to that collected in a previous study of pulvinocortical connections (Chomsung et al, 2010 We also found that the synapses formed by pulvinocortical terminals are more complex (perforated or multiple) than those formed by geniculocortical terminals, and whereas pulvinocortical terminals do not contact any GABAergic profiles, approximately 9% of geniculocortical terminals contact GABAergic profiles. Finally, we found that the horizontal orientation of layer IV geniculocortical terminals is quiet distinct from the more vertically oriented pulvinocortical terminals.…”
Section: Comparison Of Geniculocortical and Pulvinocortical Terminalsmentioning
confidence: 52%
See 2 more Smart Citations
“…We compared the data collected in the present study to that collected in a previous study of pulvinocortical connections (Chomsung et al, 2010 We also found that the synapses formed by pulvinocortical terminals are more complex (perforated or multiple) than those formed by geniculocortical terminals, and whereas pulvinocortical terminals do not contact any GABAergic profiles, approximately 9% of geniculocortical terminals contact GABAergic profiles. Finally, we found that the horizontal orientation of layer IV geniculocortical terminals is quiet distinct from the more vertically oriented pulvinocortical terminals.…”
Section: Comparison Of Geniculocortical and Pulvinocortical Terminalsmentioning
confidence: 52%
“…We compared the features of the 311 geniculocortical synapses examined in this study to 444 pulvinocortical synapses examined in the previous study from our laboratory (Chomsung et al, 2010). The size of geniculocortical terminals (mean area 1.06 ± 0.58 µm 2 ) was significantly (p < .001) larger than the size of pulvinocortical terminals (0.51 ± 0.28 µm 2 ).…”
Section: Comparison Of the Synaptic Targets Of Geniculocortical Termimentioning
confidence: 86%
See 1 more Smart Citation
“…In general, the tectorecipient pulvinar subdivisions receive afferent projections that originate exclusively from layer VI of the extrastriate cortex (Kawamura and Diamond, 1978;Chomsung et al, 2010).…”
Section: Categories Of Thalamic Nucleimentioning
confidence: 99%
“…Lyon et al (2003b) subsequently used retrograde tracing techniques to uncover pathways from PO to temporal cortical areas TP and TPI, from PC to temporal cortical area TD and from PP to temporal cortical areas TA, TI and TAL. Most recently, Chomsung et al (2010) used anterograde tracing techniques to establish that projections from the PO and PC define two areas within the temporal cortex ventrorostral to the V2 border, one caudal and one rostral. That study did not differentiate the architectonic temporal lobe areas along that border.…”
Section: Introductionmentioning
confidence: 99%